Prevalence of dual endocrinopathy: hypothyroidism and gestational diabetes mellitus in patients of preeclampsia - Gupta, Natasha; Sharma, Sudhaa; Jamwal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertension associated with proteinuria greater than 0.3g/L in a 24-hour urine collection or 1+ by qualitative urine examination, after 20 weeks of gestation is preeclampsia. The present study was conducted to evaluate prevalence of dual endocrinopathy (hypothyroidism and gestational diabetes mellitus) in patients of preeclampsia. Methods: The observational study was conducted within a period of one year from November 2015 to October 2016 in the Department of Obstetrics and Gynaecology SMGS Hospital, GMC, Jammu. A total of 400 patients of preeclampsia were included in the study and underwent serum TSH and oral glucose tolerance test. Results: In this study 32.5% of the preeclampsia patients (130 out of 400) had hypothyroidism, 15.25% patients (61 out of 400 preeclampsia) had gestational diabetes mellitus, 9.75 % patients of preeclampsia had dual endocrinopathy (both hypothyroidism and gestational diabetes mellitus). Conclusions: The current study concluded that dual endocrinopathy (both hypothyroidism and gestational diabetes mellitus) has substantially higher prevalence (9.75%) in the patients of preeclampsia.